Thyroid Eye Disease and Rare Manifestations of Severe Restrictive Strabismus with Large Hypertropia: A Case Report and Treatment Considerations: Poster Presentation - Case Report - General practitioner - Akla, Nurul; Bakri, Annisa; Sulistyowati, Balgis Desy; Janani, Nazhira (Majalah Oftalmologi Indonesia, 2023)
Introduction : Restrictive strabismus with large hypertropia is an infrequent manifestation of thyroid eye disease that arises due to severe thickening of the superior rectus muscle. This condition can lead to losing the visual axis in the primary gaze position, and prompt management is essential. Case Illustration : A Forty-seven-year-old man came to the hospital and presented with misalignment in both eyes, known for five months before admission. Ophthalmology examination revealed visual acuity for both eyes was 0.4—Large hypertropia with 50 prism diopters and exotropia with 20 prism diopters, and down shoot restrictions were found in both eyes. The patient had a history of hyperthyroidism since eight months ago and regularly took PTU medication. CT scan of the orbit showed hypertrophy on the extraocular muscle. Discussion : Continued fibroblast stimulation results in collagen deposition and subsequent fibrosis, ultimately leading to restrictive strabismus in TED patients. For patients with large hypertropia, the primary surgical approach remains recession of the involved restricted muscles, with or without tendon elongation surgery. Vertical rectus muscle resection is preferred for its low inflammation and restriction risk, while hemi hang-back is another suitable option. Conclusion : The recession of restricted muscles and tendon elongation, preferably vertical rectus muscle resection, is necessary for patients with rare manifestations of restrictive strabismus and large hypertropia in thyroid eye disease.